Determinants of Elevated Gentamicin Trough Concentrations among Neonates Receiving Once-Daily Therapy: A Prospective Cohort Study in Tanzania - Masanyiwa James; Anthony Liwa; Deogratius Bintabara; Philip Sasi (AlQalam Journal of Medical and Applied Sciences, 2026)
Neonatal sepsis remains a major cause of morbidity and mortality, particularly in low-resource settings. Gentamicin is widely used for treatment; however, its narrow therapeutic index and variable neonatal pharmacokinetics increase the risk of accumulation and toxicity. Therapeutic drug monitoring is rarely available in Tanzania. Identifying factors associated with elevated gentamicin concentrations may support safer antibiotic use where therapeutic drug monitoring is unavailable. This study aimed to identify factors associated with elevated gentamicin trough concentrations among term neonates receiving once-daily intravenous gentamicin. This sub-study was nested within a prospective observational cohort evaluating the pharmacokinetics and safety of once-daily intravenous gentamicin at doses of 4 mg/kg and 5 mg/kg among term neonates with sepsis. A total of 250 neonates receiving gentamicin were included. Trough concentrations were measured at steady state, five minutes before the fourth dose. An elevated trough concentration was defined as >2 µg/mL. Factors associated with elevated trough concentrations were assessed using multivariable logistic regression, with adjusted odds ratios and 95% confidence intervals. Elevated trough concentrations occurred in 27.2% of neonates. Independent factors associated with elevated trough concentrations included age